Reappraisal of the clinical pharmacology of low‐dose aspirin by comparing novel direct and traditional indirect biomarkers of drug action. (18th July 2014) - Patrignani, P.; Tacconelli, S.; Piazuelo, E.; Di Francesco, L.; Dovizio, M.; Sostres, C.; Marcantoni, E.; Guillem‐Llobat, P.; Del Boccio, P.; Zucchelli, M.; Patrono, C.; Lanas, A.
Summary Background Even though the acetylation of platelet cyclooxygenase (COX)‐1 at serine‐529 is the direct mechanism of action of low‐dose aspirin, its antiplatelet effect has been characterized using indirect indexes of COX‐1 activity. Objectives We performed a clinical study with enteric‐coated low‐dose aspirin (EC‐aspirin), in healthy subjects, to evaluate the effects on the extent and duration of platelet COX‐1 acetylation, using a novel proteomic strategy for absolute protein quantification (termed AQUA), as compared with traditional pharmacokinetic and pharmacodynamic parameters. Subjects and methods In a phase I, single‐arm, open‐label study of EC aspirin (100 mg day−1) administered to 24 healthy subjects, we compared, over a 24 h‐period on day 1 and 7, % platelet acetylated COX‐1 (AceCOX‐1) with traditional pharmacokinetic and pharmacodynamics [i.e. serum thromboxane (TX) B2, platelet function by monitoring CEPI(collagen/epinephrine) closure time (CT) using whole‐blood PFA‐100 and urinary excretion of 11‐dehydro‐TXB2] parameters. Results Acetylation of platelet COX‐1 was measurable before detection of aspirin levels in the systemic circulation and increased in a cumulative fashion upon repeated dosing. After the last dose of EC‐aspirin, %AceCOX‐1, serum TXB2 and CEPI‐CT values were maximally and persistently modified throughout 24 h; they averaged 76 ± 2%, 99.0 ± 0.4% and 271 ± 5 s, respectively. EC‐aspirin caused 75% reduction in urinary 11‐dehydro‐TXB2 excretion. After chronic dosing with aspirin, the pharmacokinetics of acetylsalicylic acid was completely dissociated from pharmacodynamics. Conclusions The demonstrated feasibility of quantifying the extent and duration of platelet COX‐1 acetylation will allow characterizing the genetic, pharmacokinetic and pharmacodynamic determinants of the inter‐individual variability in the antiplatelet response to low‐dose aspirin as well as identifying extra‐platelet sites of drug action.